2018
DOI: 10.1016/j.compfluid.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A high-order nonconservative approach for hyperbolic equations in fluid dynamics

Abstract: It is well known, thanks to Lax-Wendroff theorem, that the local conservation of a numerical scheme for a conservative hyperbolic system is a simple and systematic way to guarantee that, if stable, a scheme will provide a sequence of solutions that will converge to a weak solution of the continuous problem. In [1], it is shown that a nonconservative scheme will not provide a good solution. The question of using, nevertheless, a nonconservative formulation of the system and getting the correct solution has been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 21 publications
0
55
0
Order By: Relevance
“…We have developed a general technique to guaranty that the discretisation of a conservative hyperbolic problem is consistent with an additional conservation relation. This is a generalisation of the work [34] and a sequel of [32]. This construction uses in depth a reinterpretation of conservative schemes as Residual distribution schemes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We have developed a general technique to guaranty that the discretisation of a conservative hyperbolic problem is consistent with an additional conservation relation. This is a generalisation of the work [34] and a sequel of [32]. This construction uses in depth a reinterpretation of conservative schemes as Residual distribution schemes.…”
Section: Resultsmentioning
confidence: 92%
“…The equality, together with the remark of the appendix B shows that we get indeed local conservation of the entropy, too. Following [33,34],the idea is to write:…”
Section: Construction Of Entropy Conservative Schemesmentioning
confidence: 99%
“…There is no ambiguity in the definition of the last integral in (8c) because u is continuous across ∂K and the numerical fluxτ n is well defined. 4 Hereafter, we use the notation K i to indicate that the summation is done over all elements K containing a degree of freedom i 4. Residual distribution scheme.…”
Section: Staggered Grid Formulationmentioning
confidence: 99%
“…This modified form of NS equations written in Equation (4) only fulfills rigorous conservation at infinite resolution, and it has been shown that the numerical solutions of such a system might fail in converging to the correct weak solutions in the vicinity of shock discontinuities . Recent progress in solving this system was made by using a residual distribution formulation . Nonetheless, the applications of our particular interests would be smooth flows but might involve multiphysics and complex nonlinear dynamics.…”
Section: Governing Equationsmentioning
confidence: 99%